Polar Influence of Code-Switching on Oral Communication Skills: The Case of Philippine Cebuano-Visayan Bilinguals - Olitres, Bee Jay (ETERNAL (English, Teaching, Learning, and Research Journal), 2023)
Linguists are explicitly divided on code switching's (CS hereinafter) effect on the oral communication skills of English language learners. Some studies asserted that CS is beneficial (positive) while others criticized its negative impact on the target language (TL hereinafter) proficiency in communication skills. This study examined the influence of CS strategy on the oral communication skills of bilingual Cebuano-Visayan Senior High School students of the University of Cebu - Banilad, Cebu City, Philippines. This serves to bridge the ongoing debate and as a recent contributing perspective on the CS phenomenon, especially the English and Cebuano-Visayan language pair not yet explored in a conversational analysis in a new dialectal context (locale). Employing a case study design with 9 participants for data saturation, real-life conversations of students and teachers in English classrooms were audio-recorded for one month, and triangulated with interviews and observations. Thematic and conversational analysis then ensued which yielded the finding that CS adversely affects the students' oral communication skills in the areas of morphology, phonology, and syntax but positively facilitates the strategic competence of the bilingual oral communicators. CS, therefore, has a polar influence (both positive and negative) on the student’s oral communication skills.